Design and Application of the Network Control System forAutonomous-rail Rapid Tram - LI Yiye; SU Aijun; CHENG Yuxi; SHEN Mengyu; ZOU Zhirong; TANG Penghui (Kongzhi Yu Xinxi Jishu)
Train control and management system(TCMS) is a core component for the intelligence and safety of rail vehicles. Based on the data transmission and control requirements of a new type of urban rail transit vehicle, autonomous-rail rapid tram, this paper introduced a dedicated train control management system that complies with real-time Ethernet based TCMS standards. It outlined the components of the network control system for autonomous-rail rapid tram, and introduced the feature development for this cross-border and innovative trafic tool, including double ring network topology and real time Ethernet control. Finally, it looked forward to the technology development trend of the TCMS for autonomous-rail rapid tram.